Resveratrol promotes the polarization of rat microglial cell line to M2 type with oxygen glucose deprivation/reoxygenation via up-regulating the expression of annexin A1 - LIN Min, ZHANG Hong-mei (Jichu yixue yu linchuang, 2021)
Objective To explore the role of annexin A1 (ANXA1) in resveratrol regulation of M2 type polarization of rat microglial cell line with oxygen glucose deprivation/reoxygenation (OGD/R) model. Methods Lentivirus LV-shAnxA1 was used to silence the expression of AnxA1 in N9 cells. LV-Scramble acted as a control lentivirus. Western blot and RT-qPCR were used to verify the efficiency of lentivirus infection. 3 d after lentivirus infection, the N9 cell OGD/R model was constructed. 3 days after reoxygenation, the cells were treated with resveratrol for 24 hours. The groups were as follows: OGD/R(-) group, OGD/R(+) group, OGD/R(+)+Res group, OGD/R(+)+Res+LV-Scramble group, OGD/R(+)+Res+LV-shAnxA1. RT-qPCR and Western blot were used to detect the mRNA and/or protein content of ANXA1, CD11b, tumor necrosis factor (TNF-α), Interleukin-1β(IL-1β), arginase-1 (Arg-1) and Interleukin-10 (IL-10). Immunofluorescence was applied to observe the distribution of ANXA1 in cells. Results The level of ANXA1 mRNA and protein in OGD/R(+)+Res group was significantly higher than that in OGD/R(+) group. The ANXA1 protein in the OGD/R(+) group was mainly distributed in the nucleus,while the ANXA1 protein in the OGD/R(+)+Res group was mainly distributed in cytoplasm. After inhibiting the expression of ANXA1, the OGD/R(+)+Res+LV-shAnxA1 group ANXA1 was mainly located in the nucleus. Compared with the OGD/R(+)+Res group, the CD11b protein content in the OGD/R(+)+Res+LV-shAnxA1 group was significantly increased (P＜0.01), and the TNF-α and IL-1β mRNA levels were significantly increased(P＜0.001), while Arg-1 and IL-10 mRNA levels were significantly reduced. Conclusions Resveratrol promotes the polarization of rat microglial cell line wih OGD/R model to M2 type via upregulation of ANXA1 expression.